2023
DOI: 10.1002/btm2.10492
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for mRNA‐based therapeutics: Challenges and opportunities

Abstract: Messenger RNA (mRNA) holds great potential in developing immunotherapy, protein replacement, and genome editing. In general, mRNA does not have the risk of being incorporated into the host genome and does not need to enter the nucleus for transfection, and it can be expressed even in nondividing cells. Therefore, mRNA‐based therapeutics provide a promising strategy for clinical treatment. However, the efficient and safe delivery of mRNA remains a crucial constraint for the clinical application of mRNA therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 236 publications
(485 reference statements)
0
8
0
Order By: Relevance
“… 182 The above results indicate that EVs are superior carriers for the delivery of mRNA because they can prevent the mRNA from sensitive enzymatic degradation in the circulation, thus achieving a high stability after administration. 183 …”
Section: Evs As Gene Drug Delivery Vehiclesmentioning
confidence: 99%
“… 182 The above results indicate that EVs are superior carriers for the delivery of mRNA because they can prevent the mRNA from sensitive enzymatic degradation in the circulation, thus achieving a high stability after administration. 183 …”
Section: Evs As Gene Drug Delivery Vehiclesmentioning
confidence: 99%
“…The long-term storage of mRNA therapeutic agents and their distribution in areas with limited infrastructure for cold chain storage can be challenging. 95 Furthermore, ensuring that polypeptide-based mRNA delivery systems are manufactured consistently with a high standard of quality is essential for their successful application in therapeutic settings. The Food and Drug Administration (FDA) requires that manufacturers adhere to current Good Manufacturing Practice (cGMP) regulations, which outline specific guidelines for the manufacturing, testing, and quality control of drugs and medical devices.…”
Section: Challenges Against Polypeptide-based Mrna Deliverymentioning
confidence: 99%
“…Although CRISPR/Cas9 system can be packaged into sEVs by physical methods including electroporation, these approaches could be inefficient, so genetically engineered sEVs have been devised as novel packaging strategies to facilitate cargo loading of sEVs-mediated CRISPR/Cas9 deliver [22][23][24][25][26]. Ye et al, demonstrated that efficient packaging was achieved in vitro by the fusion between GFP and GFP nanobody in GFP-expressing sEV protein CD63 and GFP nanobody-expressing Cas9 protein [27].…”
Section: Ivyspringmentioning
confidence: 99%